Exploring the Influence of the Environment on Students’ Second Language Acquisition: A Comprehensive Psycholinguistic Study - Jefriyanto Saud; Lela Susanty; Petrus Jacob Pattiasina; Satriani; Wajnah (RETORIKA: Jurnal Ilmu Bahasa, 2023)
Al-Maliki 2 Sukodono Islamic Boarding School employs a distinctive approach by implementing a bilingual education system using both English and Arabic languages. However, in this regard, there are several obstacles, namely lack of students’ enthusiasm, inconsistency, lack of interest and family support, as well as limited facilities. Therefore, to address these issues, a concept is introduced that every student who wishes to become a member of that community is required to use the same language, either English or Indonesian. Furthermore, the reserach aims to demonstrate various types of motivation that can be employed by educators, institutions, and parents. Al-Maliki 2 Sukodono Islamic Boarding School implements bilingual education, incorporating both English and Arabic for communication. However, throughout this process, several barriers hinder the students, such as a lack of interest in foreign languages and inadequate support from families with no foreign language background. This research explores the process of acquiring English as a second language for students and emphasizes the significance of the environment in second language learning. Data can be collected through speaking or writing tasks, where participants are asked to generate specific language. This aids in understanding the language production process, planning, and decision-making involved in selecting words and sentence structures. The findings of this research are expected to assist schools and non-formal institutions as organizers in identifying motivational approaches that can be applied to students in English language learning. Ultimately, this can lead to improved quantity and quality of students’ English language proficiency, fulfilling Indonesia’s workforce demands.